1994
DOI: 10.1128/iai.62.2.615-622.1994
|View full text |Cite
|
Sign up to set email alerts
|

Structures of cell wall mannans of pathogenic Candida tropicalis IFO 0199 and IFO 1647 yeast strains

Abstract: We conducted a structural analysis of the cell wall mannans isolated from two Candida tropicalis strains, IFO 0199 and IFO 1647, exhibiting strong agglutinabilities against anti-Candida factor sera 5 and 6. The products released from these mannans by acid treatment were identified as the oligosaccharides, from biose to pentaose, consisting solely of "-1,2-linked mannopyranose units corresponding to common epitopes of Candida albicans serotypes A and B (factor 5). Mild acetolysis of acidand alkali-treated manna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 44 publications
(49 reference statements)
2
37
0
Order By: Relevance
“…β‐1,2 linked mannosides are uncommon glycosidic structures whose presence has never been reported in mammals so far but which have been evidenced as dispersed linkages in complex heteropolymers of some bacterial species [23, 24]. These linkages are more common in yeasts and especially in the mannan of Candida species where they are present at the reducing end of acid‐stable α linked oligomannosides [9, 25–28] or as phosphate bound acid‐labile homopolymers [9, 29, 30]. These two classes of oligomers support respectively the specificity of the factor sera 6 and 5 [31, 32] from the Candida Check, a commercially available kit intended for the identification of medically important Candida species.…”
Section: Discussionmentioning
confidence: 84%
“…β‐1,2 linked mannosides are uncommon glycosidic structures whose presence has never been reported in mammals so far but which have been evidenced as dispersed linkages in complex heteropolymers of some bacterial species [23, 24]. These linkages are more common in yeasts and especially in the mannan of Candida species where they are present at the reducing end of acid‐stable α linked oligomannosides [9, 25–28] or as phosphate bound acid‐labile homopolymers [9, 29, 30]. These two classes of oligomers support respectively the specificity of the factor sera 6 and 5 [31, 32] from the Candida Check, a commercially available kit intended for the identification of medically important Candida species.…”
Section: Discussionmentioning
confidence: 84%
“…This complexity is multiplied by secondary and tertiary structural considerations also implicit in the relatively simple, linear structures of proteins and nucleic acids. The wealth of variation in wall carbohydrates is increasingly being used to facilitate yeast taxonomy (Depree et a1.,1993;Prillinger et al, 1993;Kobayashi et al, 1994).…”
Section: Structure Of the Cell Wallmentioning
confidence: 99%
“…Kobayashi et al [12] showed that cells of C. tropicalis IFO 0199, IFO 0589, IFO 1400 and IFO 1647 are clearly aggregated with FAbs 1, 4, 5, and 6, and they reported that it the same as those of C. albicans serotype A (J-1012 strain) cells.…”
Section: Introductionmentioning
confidence: 99%
“…These FAbs recognize the antigenic determinants in cell wall mannan [11]. We reported the structure of cell wall mannans of several Candida species, including C. tropicalis [12], C. albicans [13] [14], C. glabrata [15], C. guilliermondii [16], and C. krusei [17]. Moreover, we revealed that the determinants of antigenic factors 5, 6, and 9 correspond to the oligomannosyl side chains consisting of a homologous β-1,2-linked series [18], of β-1,2 and α-1,2-linked mannose residues [19], and of β-1,2 and α-1,3-linked mannose residues [20] [21], respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation